PENERAPAN MODEL PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD NEGERI 03 LUBUKLINGGAU - Putri, Karunia; Erwandi, Rudi; Rijal, Akmal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether the application of the Teams Games Tournament (TGT) Learning model can complate the learning outcomes of pancasila education for foutrh-grade students at SD Negeri 3 Lubuklinggau. This research method used an experimental research method with a pre-test and post-test experimental design. Sampling was taken using the side random technique,. The sample in the study was 30 students of class IV.B. The instrument used by the researcher was a multiple-choice questionnaire with 10 questions. Data collection was carried out using a test technique. Data were analyzed using the t- test formula. Based on the results of the hypothesis test, the calculated t_value is then consulted with the t_(table) in the t distribution list with a significance level of α = 0.05 so that the calculated t_value> t_table (5,36> 1.69) is obtained. With this, H_0 is rejected and H_a is accepted. So it can be concluded that the Make A Match learning model can complete the science learning outcomes of Teams Games Tournament (TGT) students of SD Negeri 03 Lubuklinggau.